The Importance of Witness A De Charge as Evidence for the Defendant in the Crime of Domestic Violence (KDRT) (Case Study of Decision No. 3339/Pid.Sus/2018/PN.Sby) - Hikmah Istiqomah; Waluyo (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2024)
Abstract Introduction to the Problem: The law was created to regulate and protect all components of society. The preamble of Law of the Republic of Indonesia Number 8 of 1981 point C concerning Criminal Procedure Law explains that national development in the field of criminal procedure law is intended to make the community appreciate their rights and obligations and to improve the attitude of law enforcers and the protection of human dignity, order and legal certainty for the implementation of the rule of law in accordance with the 1945 Constitution. Purpose/Study Objectives: This research aims to find out how important the position of witness a de charge is for the defendant in the crime of domestic violence. Design/Methodology/Approach: This research uses normative juridical research methods. Data collection was carried out by means of literature and document studies. Data analysis was carried out using analytical descriptive methods and using a qualitative approach. Findings: The results showed that there is a right to submit witnesses or experts that have been given by the law by the suspect or defendant as referred to in Article 65 of the Criminal Procedure Code, so that the examiners at all levels of examination are obliged to ask the suspect or defendant, but there is no obligation for the defendant to present witnesses in the trial so that it will not affect the legal status of the defendant. Paper Type: Research Article